(untitled) (KYAMC Journal, 2023)
Background: Microalbuminuria is a microvascular complication of diabetes mellitus. Physical exercise has effects on urinary albumin-creatinine ratio and blood pressure in type 2 diabetic male with microalbuminuria. Objective: To assess the effects of physical exercise on urinary albumin-creatinine ratio and blood pressure in type 2 diabetic male with microalbuminuria. Materials and Methods: This prospective interventional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka between 1st July 2015 and 30th June 2016. Total thirty (30) type 2 diabetic male with newly diagnosed microalbuminuria (urinary albumin-creatinine ratio 30-299 mg/g), age ranged from 45 to 60 years were selected by purposive consecutive sampling from Out Patient Department of Endocrinology, Sir Salimullah Medical College and Mitford Hospital, Dhaka. Previously prescribed oral hypoglycemic and antihypertensive drugs were maintained, and the participants were instructed not to change their diet habits during the study period. All the participants were asked to perform moderate aerobic physical exercise, consisting of 30-40 minutes walking/day, 5 days/week, at an intensity of 50-70% of maximum heart rate (HRmax) for a total duration of 90 days. All the subjects were studied two times: before performing physical exercise i.e. on day-1 (Phase A) and after performing physical exercise for 90 days i.e. on day-91 (Phase B). Urinary creatinine level was estimated by fix time kinetic method and urinary albumin level was estimated by immunometric assay method. Urinary albumin-creatinine ratio was measured by calculation. Moreover, blood pressure was also measured. For statistical analysis, paired sample “t” test was performed. Results: In this study, urinary albumin-creatinine ratio, systolic and diastolic blood pressure were significantly (p<0.001) decreased in type 2 diabetic male with microalbuminuria after performing physical exercise for 90 days in comparison to those of their pre exercise values. Conclusion: From this study it may be concluded that, physical exercise significantly decreased urinary albumin-creatinine ratio, systolic and diastolic blood pressure in type 2 diabetic male with microalbuminuria. KYAMC Journal Vol. 14, No. 01, April 2023: 25-29